Study of activities at Jurong Port main gate (general and bulk cargo) - Shum, Qin Ying. (2011)
Intermodal transportation is increasingly popular because of globalisation and the flexibility it allows. Ports are the intermodal transfer points for sea to land and vice versa, and swift modal transfers are the key to competitiveness. Congestion at port gates may occur as a result of ineffective port planning, enhanced security measures (increased documentation procedures) and slow maneuver of heavy vehicles. The project focuses on Jurong Port Main Gate, in the outbound direction, which provides clearance for imported general and bulk cargoes. The cargo documentation process will be studied, along with other safety and security measures taken by the port. A short case study will be done on one of Jurong Port’s customer, Holcim, to understand the documentation process of cement companies. Lastly, analysis of the total outbound volume, along with queues, arrival rates and service times for one typical day will be done. Peak Hour Factor and Queuing Theory model will be used to illustrate the analysis. The cargo entry/exit system implemented by the port has good documentations which fulfill its purpose of effective tracking of cargoes and people. Vehicles generally follow the allocation of lanes, signifying the good design and planning of the gate. Recommendations include a simulation model to estimate vehicle traffic, mobile application to allow real time access to JP-Online, and enabling storage of bar-coded documents in mobile phones.